Risk Factors for the Incidence of Drug-Resistant Tuberculosis in the Labuang Baji Hospital: A Healthpreneur Perspective - Rahmat, Afiyah Mahdiyah; Noor, Nur Nasry; Maria, Ida Leida; Davies, George (Pandawan, 2024)
Tuberculosis (TB) caused by Mycobacterium tuberculosis, remains a global health challenge, with drug-resistant TB (TB-RO) posing significant risks to control efforts. This study aims to identify risk factors associated with TB-RO among patients at Labuang Baji Makassar Hospital, Indonesia. Conducted from September to October 2023, this analytical case-control study utilized a quantitative approach. Data were collected from the Tuberculosis Information System (SITB) and hospital medical records, involving all TB-RO patients under treatment between 2022 and 2023. Total sampling yielded 105 cases, with analysis performed using univariate, bivariate, and multivariate methods. Results indicate that age (OR=2.509, CI 95%: 1.120–5.622; p=0.036), positive BTA sputum (OR=3.397, CI 95%: 1.630–7.082; p=0.001), and prior treatment history (OR=0.461, CI 95%: 0.254–0.837; p=0.016) are significant factors. Positive BTA sputum emerged as the dominant risk. Findings suggest that inadequate treatment adherence may contribute to TB-RO incidence. The study concludes that age and BTA phlegm are key risk factors, while a history of successful treatment is protective. Strengthening patient monitoring and ensuring treatment compliance are essential for mitigating TB-RO risk and improving outcomes.